Legal Analysis of Family Maintenance in Labor Dynamics: A Review of Contemporary Family Law - Dewa Sukma Kelana; Sahrul Hanafi; Beni Ahmad Saebani; Idzam Fautanu (IJoIS: Indonesian Journal of Islamic Studies, 2026)
Transformations in the labor market and shifts in the family law paradigm have blurred the concept of spousal support, which remains rooted in the male breadwinner paradigm. This study analyzes the dynamics of spousal support rights and obligations in the context of modern employment and identifies gaps in policy and judicial responses. Using a normative legal method with a legislative, conceptual, and case-law analysis approach covering the 2020–2025 period, the data were examined qualitatively through the harmonization of legal norms and the extraction of the ratio decidendi. The results indicate: (1) the legal framework for spousal support has not yet internalized the principle of shared responsibility or recognized the economic value of domestic labor; (2) the fragmentation of jurisprudence between Religious Courts and Industrial Relations Courts (PHI) in addressing the income volatility of non-standard workers creates legal uncertainty; and (3) labor regulations remain individualistic and disregard household resilience. The concepts of a living wage and household-centered responsibility are operationalized as parameters for adjusting obligations based on real economic capacity, childcare time allocation, and dependency ratios. The novelty of this study lies in the integration of family and labor law through a household resilience framework. Policy reforms are urgently needed to prevent the feminization of poverty and to create a gender-just labor ecosystem.